The limits of power and the balance of interests: An analysis of the areas of influence of corrective powers in the hegemony system. (قضايا سياسية, 2025)
A review of an article titled (The Limits of Power and the Balance of Interests: An Analysis of the Fields of Influence of Revisionist Powers in the Hegemonic System) published in: Prof. Dr. Suhad Ismail Khalil: Al-Alamain Institute Journal, Issue (8), 31/3/2022 https://j.alalamain.edu.iq/index.php/almahad/article/download/140/496/862